Antimicrobial stewardship: Attitudes and practices of healthcare providers in selected health facilities in Uganda - Kimbowa, Isaac Magulu; Eriksen, Jaran; Nakafeero, Mary; Obua, Celestino; Lundborg, Cecilia Stålsby; Kalyango, Joan; Ocan, Moses (PloS one, 2022)
Though antimicrobial stewardship (AMS) programmes are the cornerstone of Uganda’s national action plan (NAP) on antimicrobial resistance, there is limited evidence on AMS attitude and practices among healthcare providers in health facilities in Uganda. We determined healthcare providers’ AMS attitudes, practices, and associated factors in selected health facilities in Uganda. We conducted a cross-sectional study among nurses, clinical officers, pharmacy technicians, medical officers, pharmacists, and medical specialists in 32 selected health facilities in Uganda. Data were collected once from each healthcare provider in the period from October 2019 to February 2020. Data were collected using an interview administered questionnaire. AMS attitude and practice were analysed using descriptive statistics, where scores of AMS attitude and practices for healthcare providers were classified into high, fair, and low using a modified Blooms categorisation. Associations of AMS attitude and practice scores were determined using ordinal logistic regression. This study reported estimates of AMS attitude and practices, and odds ratios with 95% confidence intervals were reported. We adjusted for clustering at the health facility level using clustered robust standard errors. A total of 582 healthcare providers in 32 healthcare facilities were recruited into the study. More than half of the respondents (58%,340/582) had a high AMS attitude. Being a female (aOR: 0.66, 95% CI: 0.47–0.92, P < 0.016), having a bachelor’s degree (aOR: 1.81, 95% CI: 1.24–2.63, P < 0.002) or master’s (aOR: 2.06, 95% CI: 1.13–3.75, P < 0.018) were significant predictors of high AMS attitude. Most (46%, 261/582) healthcare providers had fair AMS practices. Healthcare providers in the western region’s health facilities were less likely to have a high AMS practice (aOR: 0.52, 95% CI 0.34–0.79, P < 0.002). In this study, most healthcare providers in health facilities had a high AMS attitude and fair AMS practice.